The relationship between dizziness and sleep: a review of the literature - van Leeuwen, Roeland B.; Schermer, Tjard R.; Bienfait, Henri P. (Frontiers in Neurology, 2024)
Background The relation between vestibular disorders and (quality of) sleep is underexplored scientifically and the complex interactions between vestibular and sleep disorders are far from being well understood. Some studies have been conducted on the association between patients with vestibular disorders and (the occurrence of) sleep disorders, other studies have been published on the prevalence of dizziness complaints in patients with sleep disorders. The quality of sleep in patients with vestibular disorders generally receives little attention in clinical practice. Objective To establish what is currently known about the mutual relationship between dizziness and sleep, and to assess whether or not there is evidence of causality with regard to this relationship. Methods After systematically searching four literature database up until 1 April 2024, selected studies were summarized and evaluated through a (critical) review. Results Ultimately, 42 studies were selected and evaluated. Patients with dizziness in general and patients with a specific vestibular disorder like Benign Paroxysmal Positional Vertigo, Vestibular Migraine, Meniere’s disease, and vestibular hypofunction were significantly more likely to have sleep disorders than control groups. A causal relationship is not supported due to the nature of the studies. In patients with obstructive sleep apnea syndrome there were significantly more vestibular complaints, and more disorders in the vestibular system were identified. Conclusion Dizziness complaints often co-exist with a sleep disorder. To what extent this sleep disorder influences dizziness is not clear. Paying attention to the quality of sleep in patients with a vestibular disorder seems to be important. In patients with OSAS, consideration should be given to vestibular complaints and dysfunction.